Policy responses to cope with COVID-19 in Viet Nam: An empirical stock-flow-consistent approach - Thi Thu Ha Nguyen; Etienne Espagne; Luis Reyes; Thi Anh-dao Tran (Asian Development Bank Institute (ADBI), 2023)
The COVID-19 pandemic has had systemic macroeconomic impacts due to the different lockdowns and the induced shocks to both supply and demand. A global recession of a magnitude probably worse than the 2008 global financial crisis is already underway. Like every country in the world, the Vietnamese Government has taken several measures to compensate for the economic damage of the COVID-19 crisis and promote the economic recovery. However, public intervention in the form of fiscal and monetary policies raises a crucial question about public debt and fiscal sustainability challenges. Hence, this study aims to analyze the different consequences of this public intervention not only on the real side of the economy but also on the financial side. We use a consistent empirical stock-flow model for the Vietnamese economy, integrating its real and financial aspects. We find that stimulus packages can be effective in the short run, even if they increase the government deficit and public debt. In the short term, the main source of financing is borrowing. However, in the medium to long term, policymakers need to think more about taxation to raise government revenues and spending policies after recovery to promote resilient and inclusive economic growth and to support fiscal sustainability.
Keywords: E62; E12; E17; 330; fiscal policy; monetary policy; post-Keynesian economics; stock-flow-consistent modeling